Perempuan Dan Sekolah Lapang Hasil Laut - Alimul Muniroh; Moh Nasrul Amin (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Economic needs urge the men as breadwinners to become migrant workers or Tenaga Kerja Indonesia (TKI) in Malaysia, including people in Pangkah Kulon village. This community service aimed at empowering women of the migrant family to manage the family economy, increase their awareness about the potential of seaweed products, and improve their ability to use seaweed products through fieldwork. Participatory Action Research (PAR) was applied in the form of collaboration between researchers and the community to research together, formulates problems, plan actions, and carry out activities continuously. The results showed that the women of migrant workers family gained awareness of the importance of increasing the use of seaweed products into processed materials that have economic value, and the importance of networking in the use of marine products. They also managed to establish a "Jamal Sejahtera" business group with superior production from processed seafood products, namely, shellfish, payus fish and gereh.